Dentigerous cyst of maxilla in a young child - Pramod, D. S. R. (Medknow Publications & Media Pvt Ltd, 2011)
Dentigerous cysts are the most common odontogenic and developmental cysts arising in the jaws. In this article, we report a rare case of dentigerous cyst arising from an unerupted canine which had invaded a part of the maxilla in a 6-year-old child. The clinical features, radiographic presentation, and the treatment modality are described.